Estudo do funcionamento do estabelecimento agrícola “sítio do Jota”, ramal do Cataiandeua, Abaetetuba-PA - PIMENTEL, Ana Laura Marinho (2023)
This report deals with the study of the functioning of the agricultural establishment located on the Cataiandeua branch, rural area of ​​Abaetetuba- PA. In a holistic way, the agricultural establishment can be seen as a system, which has relationships with its components and the surrounding environment. This work describes the information collected referring to the last agricultural cycle (June 2021 to July 2022) obtained using questionnaires, Participatory Rural Diagnosis tools, experiences and data for supervised internships II and III of the Agroecology Technology course, at the Federal University of Pará campus Abaetetuba. The objective of the report is to understand how of the Brito family's agricultural establishment, based on observation of the family trajectory and analysis of the agricultural cycle. On the property under study, decision-making is carried out with the consent of all members, aiming to achieve all the objectives proposed by the family. The production system under study is characterized by being a system in constant evolution, and this can be attributed to the opportunities offered through financing carried out within the property. These financings constitute a large investment mainly in açaí cultivation, enabling economic return to ownership and self-consumption by the family. It is concluded that carrying out the internships supervised II and III was an opportunity to observe and apply theoretical methodologies taught in the classroom, stimulating students in the reality of the work field, while allow interaction with the community and the farmers studied. In this way, the study of the agricultural establishment made it possible to identify the factors of opportunities and chances of improvement, as well as the limitations of the agricultural production unit.